2018
DOI: 10.1007/s12028-018-0582-0
|View full text |Cite
|
Sign up to set email alerts
|

Nicardipine Reduces Blood Pressure Variability After Spontaneous Intracerebral Hemorrhage

Abstract: Our study suggests patients with ICH who do not receive a nicardipine-based antihypertensive regimen have more BPV, which has been associated with poor clinical outcomes. Prospective, randomized, controlled trials are needed to determine the impact of specific antihypertensive regimens on clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
15
1
1
Order By: Relevance
“…16 Nicardipine infusion has been shown to reduce blood pressure toward this goal more rapidly, while producing less BPV than intravenous push (IVP) antihypertensive medication. [27][28][29] Although our study did not identify BPV as an independent risk factor for the outcome of mortality among patients with sICH, we identified one EPs' intervention that was associated with patients' in-hospital mortality. Starting nicardipine infusion in the ED was associated with 65% lower likelihood of death for patients.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…16 Nicardipine infusion has been shown to reduce blood pressure toward this goal more rapidly, while producing less BPV than intravenous push (IVP) antihypertensive medication. [27][28][29] Although our study did not identify BPV as an independent risk factor for the outcome of mortality among patients with sICH, we identified one EPs' intervention that was associated with patients' in-hospital mortality. Starting nicardipine infusion in the ED was associated with 65% lower likelihood of death for patients.…”
Section: Discussioncontrasting
confidence: 59%
“…Nicardipine infusion was shown to produce less BPV compared to other IVP antihypertensive medications (eg, labetalol, hydralazine). 28,29 Therefore, it is possible that patients in our study who received nicardipine infusion in the ED had less BPV and were less likely to develop hematoma expansion as well as neurological deterioration. 18,30,31 Further studies are needed to confirm our observations and to further investigate EPs' interventions and sICH patients' outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…A retrospective analysis of 272 patients diagnosed with ICH and receiving labetalol, hydralazine, and/or nicardipine within 24 hours of hospital admission evaluated their effects on BPV. 63 This study showed that nicardipine use was associated with less BPV and a higher likelihood to achieve an SBP goal lower than 140 mm Hg. Clevidipine and nicardipine were compared in a retrospective analysis of 57 neurocritically ill patients.…”
Section: Pharmacologic Agent Selectionmentioning
confidence: 68%
“…However, this study did not find a significant difference in BPV between both groups. A retrospective analysis of 272 patients diagnosed with ICH and receiving labetalol, hydralazine, and/or nicardipine within 24 hours of hospital admission evaluated their effects on BPV . This study showed that nicardipine use was associated with less BPV and a higher likelihood to achieve an SBP goal lower than 140 mm Hg.…”
Section: Blood Pressure Control In Neurologic Emergenciesmentioning
confidence: 99%
“…As various studies find associations with BPV and unfavorable outcomes, early data are evaluating medication selection and influence on BPV. In a retrospective cohort of patients with spontaneous ICH, antihypertensive regimens were evaluated for effects on BPV, which was defined as SD‐SBP within each hour in the first 24 hours . The authors compared labetalol and/or hydralazine given as intravenous push to nicardipine continuous infusion within the first 24 hours.…”
Section: Data Surrounding Blood Pressure Variabilitymentioning
confidence: 99%